Analysis of Car Bonnet Assembly W.r.t. the Mechanical Conceptual Processes and Simulation Results - Dileep P; Shivappa H. A., Preethi K., Chandan R., Byregowda K. C. (Journal of Power Electronics and Devices, 2021)
Bonnet is one of the main important components of a car at the front portion used to decorate the car and to add luxurious look. The shape of the bonnet is to be made aerodynamic in order to minimize the drag. Bonnet is used as a shield/cover to access the parts such as radiator, engine and many other components, hence the design is made in such away so that it can be easily accessible. In this project work, different materials were used for the same bonnet design and ultimately arrived at a conclusion for the stiffest bonnet. The static structural analysis is carried out on engine hood to evaluate the stresses and displacements induced in the car bonnet assembly for two different materials and the obtained results were interpreted. For designing the hood, geometric model was created using CATIA V5 R20, 3D modeler and then CAD model was imported into Hypermesh for meshing. The static and modal analysis was carried out for bonnet assembly using NASTRAN. The obtained results were viewed using Hyperview.